Processes of tourist (in)visibility of the landscapes of the North oasis of Mendoza, Argentina - Suden, Clarisa (2023)
Introduction: Tourism and landscape are presented as closely related concepts. The landscape is understood as a dynamic social construction in permanent evolution. It is valued for different purposes, among which is, precisely, its tourist value. In tourism promotion, some landscapes are selected and, consequently, others are marginalized according to the interests pursued by the social actors involved. Objective: The objective of this research article is to know the landscapes of the North oasis of Mendoza that are currently valued touristically according to the vision of government actors, both at the local and provincial level. Methodology: The research follows a quali-quantitative scheme, combining data collection techniques such as interviews and desk review. For the analysis, cartography was carried out to visualizate the components and landscapes valued for tourism. Results: There is a focus on landscapes linked to: viticulture, urbanization, San Martin and mountain feat, to the detriment of others that present a lower value allocation (railway landscapes and those of the eastern part of the oasis) and are mostly marginalized. There are similarities, but also inconsistencies within the speeches of each of the referents interviewed in relation to the information provided on the websites. Conclusions: The tourism promotion of landscapes is influenced by various interests that generate that, sometimes, it stops innovating and / or applying other strategies that would enable the integration of other territories, communities and practices marginalized, and, therefore, unknown.